Spiritual Orientation, Meaning in Life, Life Satisfaction, and Well-Being in Mothers with Disabled Children - Yilmaz, Gamze (Journal of religion and health, 2019)
This study was planned in order to investigate the relationship between spiritual orientation with meaning in life, life satisfaction and well-being in mothers with disabled children. The research was carried out with 128 mothers in a private rehabilitation center at eastern Turkey. The Spiritual Orientation Scale (SOS), Meaning in Life Questionnaire (MLQ), Life Satisfaction Scale (LSS), and Well-Being Index (WBI) were used in the data collection. The mean score of the mothers on the SOS was found to be high (89.34 ± 7.14). It was determined that as the mean scores of mothers on the SOS increased, their mean scores on MLQ, LSS, and WBI increased and that the relationship between them was significant (p < 0.05). It was found that as the spiritual orientation of the mothers increased, meaning in life, life satisfaction, and well-being increased as well.